2020
DOI: 10.26434/chemrxiv.11858010.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A New Benchmark Set for Excitation Energy of Charge Transfer States: Systematic Investigation of Coupled-Cluster Type Methods

Abstract: There are numerous publications on benchmarking quantum chemistry methods for excited states. These studies rarely include Charge Transfer (CT) states although many interesting phenomena in e.g. biochemistry and material physics involve transfer of electron between fragments of the system. Therefore, it is timely to test the accuracy of quantum chemical methods for CT states, as well. In this study we first suggest a set benchmark systems consisting of dimers having low-energy CT states. On this set, the excita… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(36 citation statements)
references
References 36 publications
6
29
1
Order By: Relevance
“…As such transition has, chemically speaking, an intermolecular nature, this outcome parallels the finding of Kozma and coworkers who found that CCSDT-3 performs better for intermolecular CTs. 84 Our TBE/cc-pVTZ of 8.15 eV is slightly smaller (larger) than previous CCSDR(3)/TZ (CASPT2/DZ) estimates.…”
Section: Dipeptide and -Dipeptidecontrasting
confidence: 68%
See 4 more Smart Citations
“…As such transition has, chemically speaking, an intermolecular nature, this outcome parallels the finding of Kozma and coworkers who found that CCSDT-3 performs better for intermolecular CTs. 84 Our TBE/cc-pVTZ of 8.15 eV is slightly smaller (larger) than previous CCSDR(3)/TZ (CASPT2/DZ) estimates.…”
Section: Dipeptide and -Dipeptidecontrasting
confidence: 68%
“…This would be detrimental for identifying CT states in some derivatives (e.g., the peptides). We note that Kozma and coworkers went for an even more radical choice (cc-pVDZ) in their recent work, 84 but we acknowledge that the basis set effects are likely larger for the intramolecular cases treated here. Of course, the absence of diffuse functions in ES calculations is likely to result in (slightly) overestimated transition energies.…”
Section: Basis Setsmentioning
confidence: 94%
See 3 more Smart Citations